2023
DOI: 10.23950/jcmk/13765
|View full text |Cite
|
Sign up to set email alerts
|

Conventional videolaryngoscope versus 3D printed videolaryngoscope

Kamil Varlık Erel,
Nagehan Ümit Karacan

Abstract: <b>Background and objectives:</b> In patients with Covid-19, using a video laryngoscope as an alternative to direct laryngoscopy is recommended to protect the intubator from infection and reduce intubation failures due to personal protective equipment. The cost of video laryngoscopes limits their availability in all healthcare institutions. The present study aimed to compare the efficacy and safety of 3D printed video laryngoscope and conventional video laryngoscope on intubation.<br /> <b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The relatively poor performance of AAB is in concordance with Ataman et al, who recently found a more than 40% lower first-pass success rate by the AAB compared to GlideScope ® in simulated normal and difficult airways [ 31 ]. Since the 3DVL is our custom-made device, its promising results could not be directly compared to previous studies, but it supports the hypothesis that 3D printing in general could deliver clinically useful VLs [ 30 , 33 ]. Lambert et al 3D printed and tested a channel-bladed “Tansen” VL, which has similar features to our 3DVL.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The relatively poor performance of AAB is in concordance with Ataman et al, who recently found a more than 40% lower first-pass success rate by the AAB compared to GlideScope ® in simulated normal and difficult airways [ 31 ]. Since the 3DVL is our custom-made device, its promising results could not be directly compared to previous studies, but it supports the hypothesis that 3D printing in general could deliver clinically useful VLs [ 30 , 33 ]. Lambert et al 3D printed and tested a channel-bladed “Tansen” VL, which has similar features to our 3DVL.…”
Section: Discussionmentioning
confidence: 89%
“…Today, 3D-printed VLs are already commercially available, yet scientific studies on performance are only sparsely published [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%